2021
DOI: 10.14797/pefd1523
|View full text |Cite
|
Sign up to set email alerts
|

Supracristal Ventricular Septal Defect Complicated by Formation of an Aorto-Right Ventricular Outflow Tract Fistula: A Rare Cause of Biventricular Enlargement

Abstract: Aorto-right ventricular outflow tract fistulas typically occur secondary to trauma, infective endocarditis, and sinus of Valsalva aneurysm rupture. We describe an unusual case of a spontaneous aorto-right ventricular outflow tract fistula in the absence of such findings, instead forming secondary to a complicating supracristal ventricular septal defect and leading to dilated cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The formation of true perimembranous aneurysm is due to the failure to close the fetal membranous ventricular septum in time after birth, the closure of the membranous portion is delayed after birth, and part of the generated membranous portion is continuously pressed under the left ventricular high pressure to form perimembranous aneurysm, leaving the top of the tumor, and the breach causes a left-to-right shunt at the ventricular level. Another common perimembranous aneurysm VSD is the so-called pseudoperimembranous aneurysm, which is a relatively immature fibrous tissue formed by the continuous proliferation and adhesion of the tricuspid valve septum, chordae tendineae, or surrounding tissue [7][8][9]. Previous study has shown that under the condition of left-to-right shunting of intraventricular blood at the level of VSD chamber, long-term high pressure impacted the inferior membrane defect, causing damage to the perimembranous tissue and the gap of the true perimembranous aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of true perimembranous aneurysm is due to the failure to close the fetal membranous ventricular septum in time after birth, the closure of the membranous portion is delayed after birth, and part of the generated membranous portion is continuously pressed under the left ventricular high pressure to form perimembranous aneurysm, leaving the top of the tumor, and the breach causes a left-to-right shunt at the ventricular level. Another common perimembranous aneurysm VSD is the so-called pseudoperimembranous aneurysm, which is a relatively immature fibrous tissue formed by the continuous proliferation and adhesion of the tricuspid valve septum, chordae tendineae, or surrounding tissue [7][8][9]. Previous study has shown that under the condition of left-to-right shunting of intraventricular blood at the level of VSD chamber, long-term high pressure impacted the inferior membrane defect, causing damage to the perimembranous tissue and the gap of the true perimembranous aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Underassessment and mischaracterization of VSDs, specifically outlet VSDs and peripheral aortic valve anatomy, can lead to missed pathology that would require surgical VSD closure or device closure intervention. 21,22 In addition to aortic valve prolapse and AR, a sinus of Valsalva aneurysm (SOVA) is another condition that can be caused by an outlet VSD that compromises the integrity of the ventricular septal wall. 23,24…”
Section: Discussionmentioning
confidence: 99%